Evaluation of the quality of life in patients with alopecia areata and androgenetic alopecia - I. N. Kondrakhina; A. N. Mareeva (Vestnik Dermatologii i Venerologii, 2017)
State Research Center of Dermatovenereology and Cosmetology, Ministry of Healthcare of the Russian Federation